Linguistic features of self-repair strategies of Arab Speakers of English language - Alharbi, Jamilah Maflah (Technium Social Sciences Journal, 2023)
Self-repair occurring in the same turn of speaking has been subjected to analysis in studies involving first language and second language users. However, in the context of English spoken as a foreign language, the information might still need further attention. This study is conducted to first report on the self-repair strategies employed by the Arab speakers of English in the same turn of speaking and second, to describe the linguistic features of self-repair produced by the speakers. Adopting the quantitative and qualitative approaches, data for this study come from a number of videos capturing conversations in English involving Arab speakers. The conversations in the videos were later transcribed orthographically and following this, instances of self-repair were identified. Framework of self-repair strategies provided by Emrani and Hooshmand was adopted to guide the data coding while the linguistic features of self-repair in the same turn of speaking were described by looking into its context of occurrences. The first finding has shown that repetition is the most frequent type of self-repair strategy to be employed by the Arab speakers of English. This is followed by replacement, insertion, abandonment and deletion. On the other hand, the self-repair that takes place in the same turn of speaking (where trouble source can be found as well) can be marked through a number of linguistic features namely prosodic features, the presence of fillers and the repair item that comes immediately after the trouble source item. The findings have provided insight into the speakers’ ability to monitor troubles in their speech, repair the troubles and features of their self-repair which can benefit the theoretical understanding and language classroom practices.